Valorizing Olive Oil Mill Wastewater: Transforming Waste into Natural Soaps - El Abdouni Aouatif; Haboubi Chaimae; El Bastrioui Mohamed; El Ahmadi Kawthar; El ALaoui Hasnae; Achoukhi Iliass; El Hammoudani Yahya; Dimane Fouad; Haboubi Khadija (BIO Web of Conferences, 2024)
In this research, the main objective is to find a solution to the problem of olive mill wastewater (OMWW). This solution involves the recovery of liquid waste produced by the crushing units, which contain a significant amount of oily residues despite their initial treatment. The concept is based on separating these discharges into aqueous and oil phases and using the latter to manufacture natural soaps. The liquid waste from the extraction of olive oil has a significant content of oily residues, characterized by a very high acidity (2.73%), exceeding the value of edible olive oil, as well as a high saponification index (186.2 mg KOH/g), making it an ideal source of fat for saponification. The results of the valorization of the OMWW in soap manufacturing reveal several significant elements. First, following the characterization of cold and hot products, a clear preference emerges in favor of soaps made using the cold process. In addition, the production yield is notable, with a rate of 94% for cold saponification and 89.9% for hot saponification, highlighting the efficiency of the process. Finally, the study highlights the importance of the quantities of fatty acids used in the formulation of soaps. An optimal formula is identified, comprising 40% oils recovered from the OMWW, 30% olive oil, 20% cocoa oil, and 10% castor oil, demonstrating the need for a precise balance to obtain quality soaps. This study solves the problem of the OMWW by reusing them to make natural soaps, thus reducing industrial waste. It also opens up new economic opportunities by creating a profitable and environmentally responsible production chain, promoting the transition to a circular economy.